2016
DOI: 10.1177/1747493016650454
|View full text |Cite
|
Sign up to set email alerts
|

Early neurological deterioration after thrombolysis: Clinical and imaging predictors

Abstract: Early neurological deterioration is rare. It originates mainly from ischemic infarct growth rather than from hemorrhage. Concern should be highest in patients with elevated blood glucose, larger perfusion lesions and large vessel disease. Prior aspirin use increases risk of symptomatic intracerebral hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 22 publications
(31 reference statements)
7
70
1
Order By: Relevance
“…In our study, the rate of END was 14.6%, which is similar to previous results (6–38%) [18-22], although the definition of END differed between studies. Here we have chosen the cutoff of at least 2 points deterioration at the 72-h NIHSS as proposed by Siegler et al [9] that seems to be more adapted in our patients with severe strokes at admission to avoid a “ceiling effect” and to take into account END related to malignant edema.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, the rate of END was 14.6%, which is similar to previous results (6–38%) [18-22], although the definition of END differed between studies. Here we have chosen the cutoff of at least 2 points deterioration at the 72-h NIHSS as proposed by Siegler et al [9] that seems to be more adapted in our patients with severe strokes at admission to avoid a “ceiling effect” and to take into account END related to malignant edema.…”
Section: Discussionsupporting
confidence: 81%
“…Here we have chosen the cutoff of at least 2 points deterioration at the 72-h NIHSS as proposed by Siegler et al [9] that seems to be more adapted in our patients with severe strokes at admission to avoid a “ceiling effect” and to take into account END related to malignant edema. This event was strongly associated with poor functional outcome as reported in previous studies [19, 22-24]. …”
Section: Discussionsupporting
confidence: 60%
“…1,2 Although END may have straightforward causes, such as symptomatic intracerebral hemorrhage, malignant edema, and early recurrent stroke, no clear mechanism is found in ≈2/3 of END cases, to be referred to as unexplained END below. [1][2][3] We previously reported that unexplained END is associated with higher blood glucose, no previous use of antiplatelets, larger diffusion-perfusion mismatch, persistent proximal occlusion, and diffusion-weighted imaging lesion growth beyond the initial ischemic penumbra. 2,4 This led us to suggest that unexplained END is linked to secondary hemodynamic compromise in the context of persistent occlusion, with potential mechanisms including in situ thrombus extension and new embolic events in the same arterial territory.…”
mentioning
confidence: 99%
“…[8,9] The frequency of neurological deterioration in this singlecenter study was 15.4%, which was higher than that of a retrospective study which assessed deteriorations within the first two days [10] and lower than those of two prospective studies (35% and 37%, respectively). [11,12] The studies for early neurological deterioration in non- thrombolyzed patients were found to have frequencies between 13 to 37% [13][14][15][16][17] Our patients with neurological progression had worse NIHSS scores on discharge, compared to non-progressive patients (8 vs 3.7), while the NIHSS scores were not different on admission between these two groups.…”
Section: Discussionmentioning
confidence: 50%